High levels of dietary vitamin E improve the reproductive performance of female Oreochromis niloticus - doi: 10.4025/actascibiolsci.v36i1.19830 (Acta Scientiarum. Biological Sciences, 2013)
This study aimed to evaluate the effect of vitamin E on reproductive responses of female tilapia (Oreochromis niloticus). To this, isonitrogenous and isocaloric diets with different levels of vitamin E supplementation (200, 300, 400, and 500 mg kg-1) were provided to groups of females for 90 days. Supplementation positively influenced the volume of eggs produced, spawning rate, fecundity, hatching rate, average production of larvae, reproductive frequency and survival. The fertilization rate, weight, and diameter of the eggs were not affected by supplementation. This study showed that 400 mg kg-1 vitamin E in the diet during the reproductive period of female Nile tilapia are sufficient to ensure the best reproductive performance, providing efficient production of a larger number of larvae in the individuals of this species.